Brill's companion to sieges in the Ancient Mediterranean - Armstrong, Jeremy; Trundle, Matthew, 1965-2019 (Brill's companions in classical studies. Warfare in the ancient Mediterranean world ;, 2019)
"Brill's Companion to Sieges in the Ancient Mediterranean is a wide-ranging exploration of sieges and siege warfare as practiced and experienced by the cultures which lived around the ancient Mediterranean basin. From Pharaonic Egypt to Renaissance Italy, and from the Neo-Assyrian Empire to Hellenistic Greece and Roman Gaul, case studies by leading experts probe areas of both synergy and divergence within this distinctive form of warfare amongst the cultures in this broadly shared environment"--